Loss of orf3b in the circulating SARS-CoV-2 strains. Issue 1 (1st January 2020) - Lam, Joy-Yan; Yuen, Chun-Kit; Ip, Jonathan Daniel; Wong, Wan-Man; To, Kelvin Kai-Wang; Yuen, Kwok-Yung; Kok, Kin-Hang
ABSTRACT: The newly emerged betacoronavirus, SARS-CoV-2, causes the COVID-19 pandemic since December 2019 with more than 35 million laboratory confirmed human infections and over one million deaths within nine months. The genome of SARS-CoV-2 continues to evolve during the global transmission with the notable emergence of the spike D614G substitution that enhances infectivity. Some of these viral adaptations may alter not only the infectivity but also viral pathogenesis. Continuous phylogenomic analysis of circulating viral strains and functional investigation of new non-synonymous substitutions may help to understand the evolution of virus, its virulence and transmissibility. Here we describe a loss of an accessory protein orf3b (57 amino acids) in current circulating SARS-CoV-2 strains, contributing around 24% of more than 100, 000 complete viral genomes analysed. The loss of 3b is caused by the presence of an early stop codon which is created by an orf3a Q57H substitution. There is an increasing trend in the loss of orf3b which has reached 32% in May 2020. Geographically, loss of 3b is more prevalent in certain countries including Colombia (46%), USA (48%), South Korea (51%), France (66%), Saudi Arabia (72%), Finland (76%) and Egypt (77%). Interestingly, the loss of 3b coincides with the emergence of spike D614G substitution. In addition, we found that truncated orf3b has lost the interferon antagonism compared to the full-length orf3b, suggesting a loss of function by the newly adapted virus. Further investigation of orf3b deletion and spike D614G substitution on virulence and infectivity respectively will provide important insights into SARS-CoV-2 evolution.